2012
DOI: 10.1089/omi.2012.0039
|View full text |Cite
|
Sign up to set email alerts
|

A Seven-Gene Signature Aggregates a Subgroup of Stage II Colon Cancers with Stage III

Abstract: Colorectal cancer is one of the most common cancers in the world. Histological staging is efficient, but combination with molecular markers may improve tumor classification. Gene expression profiles have been defined as prognosis predictors among stage II and III tumors, but their implementation in medical practice remains controversial. Stage II tumors have been recognized as a heterogeneous group, and high-risk morphologic features have been used to justify adjuvant chemotherapy. We propose here the investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…S6 in Supplementary Appendix 1). 12,13,26,27 Patients were stratified into negative-to-low (negative) and high (positive) subgroups with regard to CDX2 and ALCAM gene-expression levels with the use of the StepMiner algorithm, implemented within the Hegemon 21 software (Fig. S7 through S10 in Supplementary Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…S6 in Supplementary Appendix 1). 12,13,26,27 Patients were stratified into negative-to-low (negative) and high (positive) subgroups with regard to CDX2 and ALCAM gene-expression levels with the use of the StepMiner algorithm, implemented within the Hegemon 21 software (Fig. S7 through S10 in Supplementary Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…This cohort included gene expression data from four publicly available NCBI-GEO data-series (GSE14333, GSE17538, GSE31595, GSE37892)(7477), and contained information on 466 unique primary colon carcinoma samples, collected from patients at various clinical stages (AJCC Stage I-IV/Duke’s Stage A-D) by five independent institutions: 1) the H. Lee Moffit Cancer Center in Tampa, Florida, USA; 2) the Vanderbilt Medical Center in Nashville, Tennessee, USA; 3) the Royal Melbourne Hospital in Melbourne, Australia; 4) the Institut PaoliCalmette in Marseille, France; 5) the Roskilde Hospital in Copenhagen, Denmark. All 466 samples contained in this subset were cross-checked to exclude the presence of redundancies/duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that UBA7 per se is not an initiating oncogene in human CRC. To address whether UBE1L has any regulatory function in human CRC, we used two recently published datasets (40,41) to compare clinical outcomes in groups of CRC patients with low or high UBA7 expression. Results from the two datasets revealed that higher expression levels of the UBE1L gene UBA7 correlated significantly with worse survival (Fig.…”
Section: Protein Isgylation Is Correlated With Patient Survival In Humentioning
confidence: 99%